The Case of a Newly Implemented Modern Management Accounting System in a Multinational Manufacturing Company - Daniel Watts; P.W. Senarath Yapa; Steven Dellaportas (Australasian Accounting, Business and Finance Journal, 2014)
Contemporary management accounting techniques (such as TQM, BSC, JIT) are widely lauded by academia but the proposed relevance to business has not necessarily the view held by industry (e.g. Burns & Vaivio, 2001; Chenhall & Langfield-Smith, 1998; Innes et al., 2000. The purpose of this article is to investigate the acquisition by a modern multi-national firm of a major IT-based management accounting program to assess the relevance and usefulness of its functionality by identifying the type(s) of systems that are utilised and the rationale for upgrading or modifying its system(s). This study relies on a single case based on two in-depth semi structured interviews with accounting and finance professionals in a multi-national manufacturing company that recently implemented a modern management accounting system. The findings indicate that despite demonstrating some relevance of the management accounting information, the manufacturer deactivated components of the system that were deemed irrelevant at particular levels of the organisation. This paper provides evidence about the non-reliance on management accounting information in a multinational company operating in Australia. The findings in the study imply that relevance is linked to implementation, planning and training will help managers to better prepare themselves in setting up contemporary management accounting systems.
Keywords: Change; IFRS; institutional; Portugal; principles; rules